The Management of Primary Hyperaldosteronism in a Poor Technology Environment. (11th May 2021) - Sossa, Jean; Avakoudjo, Dedjinnin Josue Georges; Yevi, Dodji Magloire Ines; Fanou, Lionelle; Natchagande, Gilles; Agounkpe, Michel Michael; Hodonou, Fred; Hounto, Yao Felicien; Atadokpede, Felix
Abstract : We report a case of Conn's adenoma in a 35-year-old female successfully managed in a poor hospital technology environment.